Epidemiological studies of UK test veterans: I. General description. - Kendall, G; Muirhead, C; Darby, S; Doll, R; Arnold, L; O'Hagan, J (2004)
This review gives a general account of how and why epidemiological studies of UK participants in the nuclear weapons test programme were set up. There is a short description of the circumstances in which the tests were planned and executed and a discussion of the general considerations involved in designing studies to show whether the health of test participants suffered as a result of the tests. The companion review article summarises the results of the epidemiological studies.